33.6k views
1 vote
For f(x)=4x+2 and g(x)=x^2-6, find (f+g)(x)

A) 4x^3-4
B) 4x^2-16
C) x^2+4x-4
D) x^2+4x+8

For f(x)=4x+2 and g(x)=x^2-6, find (f+g)(x) A) 4x^3-4 B) 4x^2-16 C) x^2+4x-4 D) x-example-1
User DorBB
by
4.8k points

1 Answer

3 votes

Answer:

The answer would be x^2+4x-4

Explanation:

You can solve this by plugging 4x+2 into (f+g). 4x+2 would equal f. x^2-6 would equal g. plugging them in gets you 4x+2+x^2-6. If we simplify it we would end up with x^2+4x-4

User Glorious Kale
by
5.2k points